A Transcriptomic Immunologic Signature Predicts Favorable Outcome in Neoadjuvant Chemotherapy Treated Triple Negative Breast Tumors - Pérez-Pena, Javier; Tibor Fekete, Janos; Páez, Raquel; Baliu-Piqué, Mariona; García-Saenz, José Ángel; García-Barberán, Vanesa; Manzano, Aránzazu; Pérez-Segura, Pedro; Esparis-Ogando, Azucena; Pandiella, Atanasio; Gyorffy, Balázs; Ocana, Alberto (Frontiers in Immunology, 2019)
Limited therapeutic options exist for the treatment of patients with triple negative breast cancer (TNBC) tumors beyond the administration of chemotherapy, and very recently, the approval of the anti PD-L1 inhibitor atezolizumab. Neoadjuvant chemotherapy is currently the standard of care treatment in the early stage disease, although reliable biomarkers of response have been scarcely described. In our study we explored whether immunologic signatures associated with inflamed tumors or hot tumors could predict outcome to neoadjuvant chemotherapy. Publicly available transcriptomic data of more than 2,000 patients were evaluated. ROC plots were generated to assess response to therapy. Cox proportional hazards regression was computed to explore the association between gene expression and outcomes. Kaplan-Meier plots were drawn to visualize the survival differences. Higher expression of IDO1, CXCL9, CXCL10, HLA-DRA, , ISGF-3 from the IFN gamma signature, CXCL13, HLA-E,, LAG3 and STAT1, from the expanded gene signature and GZMB from the CTL-level signature were associated with higher proportion without relapse in the first five years after chemotherapy in TNBC. The strongest effect was observed for STAT1 (p value =1.8e-05 and AUC 0.69, p=2.7e-06). The best gene-set signature to predict favorable RFS was the combination of IDO1, LAG3, STAT1 and GZMB (HR 0.28 CI 0.17-0.46 p= 9.8 E-08). However, no influence on pathological complete response (pCR) was observed. Similar, no benefit was identified in any other tumor subtype: HER2 or estrogen receptor positive. In conclusion, we describe a set of immunologic genes that predict outcome to neoadjuvant chemotherapy in TNBC, but not pCR. suggesting that this non-time to event endpoint is not a good surrogate marker to detect long term outcome for immune activated tumors.